2015
DOI: 10.1002/pits.21828
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Social and Emotional Health Survey for Five Sociocultural Groups: Multigroup Invariance and Latent Mean Analyses

Abstract: Social‐emotional health influences youth developmental trajectories and there is growing interest among educators to measure the social‐emotional health of the students they serve. This study replicated the psychometric characteristics of the Social Emotional Health Survey (SEHS) with a diverse sample of high school students (Grades 9–12; N = 14,171), and determined whether the factor structure was invariant across sociocultural and gender groups. A confirmatory factor analysis (CFA) tested the fit of the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 42 publications
7
49
0
Order By: Relevance
“…Participants responded using a four-point scale (1 = not at all true to 4 = very much true) with the exception of the gratitude and zest assets, which used a five-point response scale (1 = not at all to 5 = extremely). The SEHS-S subscales measuring the 12 social-emotional protective assets have good internal reliability (with alphas ranging from .76 in persistence and self-control to .94 in gratitude), and the alpha coefficient of the combined, overall covitality index being .93-.95 across three samples You et al, 2014You et al, , 2015. This was confirmed in the current sample (α = .95).…”
Section: Protective Assetssupporting
confidence: 68%
See 1 more Smart Citation
“…Participants responded using a four-point scale (1 = not at all true to 4 = very much true) with the exception of the gratitude and zest assets, which used a five-point response scale (1 = not at all to 5 = extremely). The SEHS-S subscales measuring the 12 social-emotional protective assets have good internal reliability (with alphas ranging from .76 in persistence and self-control to .94 in gratitude), and the alpha coefficient of the combined, overall covitality index being .93-.95 across three samples You et al, 2014You et al, , 2015. This was confirmed in the current sample (α = .95).…”
Section: Protective Assetssupporting
confidence: 68%
“…Together, these domains combine to form the second-order covitality index, which has been conceptualized as "the synergistic effect of positive mental health resulting from the interplay among multiple positive-psychological building blocks" (Furlong, You, et al, 2014, p. 119). Covitality has been associated with a number of developmental outcomes, including academic achievement, substance use, and depressive symptoms You, Furlong, Felix, & O'Malley, 2015); however, additional research is needed to understand how the configuration of the components of covitality relates to positive and negative developmental outcomes.…”
Section: Factors Protecting Adolescents From Risk Behaviors and Emotimentioning
confidence: 99%
“…These were belief-in-self, belief-in-others, emotional competence, and engaged living. You et al [6], using confirmatory factor analysis, further identified 12 subscales loading onto these four constructs. Belief-in-Self was underpinned by the three internal assets of self-awareness, selfefficacy, and persistence while Belief-in-Others was underpinned by school support, family coherence, and peer support.…”
Section: Introductionmentioning
confidence: 99%
“…The subscales measuring the 12 socialemotional protective assets had good internal reliability in the current study with alphas ranging from .76 in persistence and self-control to .94 in gratitude (see Table 1). The alpha for the covitality index was .95, comparable (.93-.95) to previous studies You et al, 2014You et al, , 2015. Based on the literature on risk factors Farrington & Loeber, 2000), each of the 12 individual assets was scored as a continuous variable.…”
Section: Methodsmentioning
confidence: 95%
“…Each of the 12 individual assets (e.g., self-efficacy) includes three items, for a total of 36 items (nine items for each of the four domains; see Table 1 for a listing the 12 assets, four domains, and item response options). The hierarchal second-order factor structure of the SEHS was established using both exploratory and confirmation factor analysis and replicated with independent samples (You, Furlong, Dowdy, Renshaw, Smith, & O'Malley, 2014;You et al, 2015). The factor structure is invariant for males and females , older and younger adolescents (You et al, 2015), and across sociocultural groups (You et al, 2015).…”
Section: Methodsmentioning
confidence: 99%